Scour Morphology Comparison Around Oblong Bridge Pier: Clear-Water and Live-Bed Flow Conditions - Darajat, Achmad Rafi’ud; Kironoto, Bambang A.; Istiarto (Civil Engineering Journal, 2026)
Bridge pier scour is a significant contributor to structural instability in riverine infrastructure, particularly in sediment-laden tropical rivers. Streamlined shapes such as oblong piers generally produce smaller scour depths than bluff-body piers, offering potential safety advantages. However, the morphological evolution of scour under different sediment-transport regimes and its implications for structural stability remain insufficiently documented. This study experimentally compares clear-water (CW) and live-bed (LB) scour around an oblong pier, with emphasis on equilibrium depth, temporal development, three-dimensional morphology, velocity structure, and safety relevance. Flume tests were performed using a 5-cm × 10-cm oblong pier under steady subcritical flow (Q = 50 L/s, h = 10 cm, d50 = 2.21 mm, Fr < 1), with CW simulated by eliminating upstream sediment supply and LB by continuous sediment recirculation. Velocity measurements using an Acoustic Doppler Velocimeter (ADV) were conducted at equilibrium scour geometry to characterize flow structures. Results show CW scour reached a deeper equilibrium (z/D = 1.70), developed 36.4% faster (T* = 666 min) than LB (z/D = 1.52, T* = 909 min). CW formed a symmetric, steep-walled scour hole with 14.1% greater volume and 15.6% wider planform area, creating an immediate risk of vertical undermining. LB produced a shallower, more elongated scour with partial downstream backfilling, leading to gradual longitudinal undermining and slower foundation settlement. Velocity measurements revealed stronger vertical and lateral fluctuations under LB, explaining its more irregular scour morphology. Although the reduced scour depth confirms previous findings for streamlined piers, the elongated downstream scour and partial backfilling under LB provide new insights for countermeasure design. Among the tested predictors, Sheppard's Equation performed best with 8% (CW) and 3% (LB) deviations. These findings confirm that streamlined oblong piers reduce the maximum scour depth compared with circular shapes, but reveal contrasting mechanisms: CW promotes rapid, concentrated erosion, whereas LB induces slower, more widespread scour. The results emphasize that countermeasure design must explicitly account for the sediment-transport regime to ensure long-term foundation stability.